VD_FINDINFO HC / 2022 / 706 vom 8. September 2022 - VD Tribunal cantonal (2022)
CONTRAT D'ASSURANCE, INCAPACITÉ DE TRAVAIL, FARDEAU DE LA PREUVE | 152 al. 1 CPC (CH), 157 CPC (CH), 308 al. 1 let. a CPC (CH), 316 al. 3 CPC (CH)